Analisis Penurunan Muka Tanah dengan Small Baseline Subset Differential SAR Interferograms di Kota Bandar Lampung - Bagas Setyadi; Rustadi Rustadi (Engineering Faculty Universitas Lampung, 2019)
Bandar Lampung is one of the cities in Indonesia, which has a potential to land subsidence due to the extraction of ground water, mining, land conversion, and geological conditions. For that reason, carried out the study of land subsidence with SBAS technique, due to the very lack of information about the symptoms of land subsidence in Bandar Lampung. In this study, 15 SAR data in 2006 to 2011 used and then combined to produce 40 interferogram then inverted resulting in a time-series deformation and deformation speed average. Velocity precision obtained with SBAS technique is highly dependent on the type of land cover in the study area, but it is known that the average of land subsidence in Bandar Lampung is about 0.06 mm/year, which is considered quite stable due to the geological structure that does not allow for the occurrence of massive consolidation process. Several areas have indications of subsidence 5 mm/year are suspected to be caused by tectonic activity and human activity (industrial, mining, extraction of groundwater, and land conversion), which then has implications for structural damage to buildings, flooding in coastal areas, and landslides in hilly areas.